Fungal Endophytes to Combat Biotic and Abiotic Stresses for Climate-Smart and Sustainable Agriculture - Verma, Anamika; Shameem, Nowsheen; Jatav, Hanuman Singh; Sathyanarayana, Eetela; Parray, Javid A.; Poczai, Peter; Sayyed, R. Z. (Frontiers in Plant Science, 2022)
The agricultural sustainability concept considers higher food production combating biotic and abiotic stresses, socio-economic well-being, and environmental conservation. On the contrary, global warming-led climatic changes have appalling consequences on agriculture, generating shifting rainfall patterns, high temperature, CO2, drought, etc., prompting abiotic stress conditions for plants. Such stresses abandon the plants to thrive, demoting food productivity and ultimately hampering food security. Though environmental issues are natural and cannot be regulated, plants can still be enabled to endure these abnormal abiotic conditions, reinforcing the stress resilience in an eco-friendly fashion by incorporating fungal endophytes. Endophytic fungi are a group of subtle, non-pathogenic microorganisms establishing a mutualistic association with diverse plant species. Their varied association with the host plant under dynamic environments boosts the endogenic tolerance mechanism of the host plant against various stresses via overall modulations of local and systemic mechanisms accompanied by higher antioxidants secretion, ample enough to scavenge Reactive Oxygen Species (ROS) hence, coping over-expression of defensive redox regulatory system of host plant as an aversion to stressed condition. They are also reported to ameliorate plants toward biotic stress mitigation and elevate phytohormone levels forging them worthy enough to be used as biocontrol agents and as biofertilizers against various pathogens, promoting crop improvement and soil improvement, respectively. This review summarizes the present-day conception of the endophytic fungi, their diversity in various crops, and the molecular mechanism behind abiotic and biotic resistance prompting climate-resilient aided sustainable agriculture.